all the terms are 3 less than its preceding term, simple!
So, the formula would be:
![a_n=a+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/t99kk5roieipg56xa37yseewl9ybc4zh6i.png)
Where
a is the first term
d is the common difference (diff in 2 terms)
From the sequnce,
first term (a) is 50
common difference (d) = 47 - 50 = -3
So, we have:
![\begin{gathered} a_n=a+(n-1)d \\ a_n=50+(n-1)(-3_{}) \\ a_n=50-3n+3 \\ a_n=53-3n \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h4gdlissjycm91xm24ibc3c62onn0jfry1.png)
Explicit Formula:
![a_n=53-3n](https://img.qammunity.org/2023/formulas/mathematics/college/90q97ckxvpqb7mmn8ldhm61rclv27eku77.png)